Faktor Resiko yang Mempengaruhi Pemanfaatan Layanan Pengantaran Obat di RSUD Balaraja Kabupaten Tangerang - Cri Sajjana Prajna Wekadigunawan; Endang Sulastri; Rini Handayani; Decy Situngkir (Malahayati Nursing Journal, 2026)
ABSTRACT Long waiting times for medication have led to long queues and increased patient complaints about pharmaceutical services. This issue has resulted in low patient satisfaction with pharmaceutical services at Balaraja Regional Hospital, as reflected in public satisfaction surveys conducted in the second half of 2024 and the first half of 2025which showed poor results.. Drug delivery services are a form of digital innovation in pharmaceutical services that aims to reduce the density of pharmacy queues and increase patient accessibility to drugs.. Balaraja Regional General Hospital, Tangerang Regency, has collaborated with JNE in providing home drug delivery services since March 2025, but the utilization rate is still low (7%) of the target of 20%. This study aims to determine the factors associated with the utilization of drug delivery services at Balaraja Regional General Hospital, Tangerang Regency in 2025. A quantitative approach was used in this study using a Cross Sectional study design. A sample of 150 respondents was selected using Purposive Sampling techniques from the entire population, namely outpatients who received prescription services, amounting to 9448. Data were collected through structured questionnaires and electronic medical records. Data analysis used Chi-Square and Prevalence Ratio (PR) statistical tests. The results of the study showed that 60.7% of respondents did not utilize the service. Variables showing significant relationships were income (p=0.029; PR=1.475), information exposure (p0.001; PR=3.017), and perception of estimated time of arrival (p=0.04; PR=1.521). Other variables, such as gender, education level, perceived cost, perceived distance, and chronic disease status, did not show significant relationships. Information exposure was the strongest factor associated with service utilization. Balaraja Regional General Hospital, Tangerang Regency, needs to improve its service socialization strategy, reduce service fees, and accelerate estimated delivery times. Keywords: Drugs Delivery Services, Healthcare Utilization, Information Exposure, Income, Perception of Estimated Time of Arrival.  ABSTRAK Lamanya waktu tunggu obat menyebabkan padatnya antrian dan meningkatkan keluhan pasien akan layanan obat.  Masalah ini mengakibatkan rendahnya kepuasan pasien akan layanan farmasi di RSUD Balaraja yang tergambar pada hasil survei kepuasan masyarakat pada periode semester II 2024 dan semester I tahun 2025 dengan hasil kurang baik . Layanan pengantaran obat merupakan bentuk inovasi digital dalam pelayanan kefarmasian yang bertujuan mengurangi kepadatan antrian farmasi dan meningkatkan aksesibilitas pasien terhadap obat. RSUD Balaraja Kabupaten Tangerang sejak Maret 2025 telah menjalin kerjasama dengan JNE dalam menyediakan layanan pengantaran obat ke rumah, namun tingkat pemanfaatannya masih rendah (7%) dari target 20%. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan pemanfaatan layanan pengantaran obat di RSUD Balaraja Kabupaten Tangerang tahun 2025. Pendekatan kuantitatif digunakan dalam penelitian ini dengan menggunakan desain studi Cross Sectional.Sampel berjumlah 150 responden yang dipilih menggunakan teknik Purposive Sampling dari seluruh populasi yaitu pasien rawat jalan yang mendapatkan pelayanan resep yaitu sejumlah 9448. Data dikumpulkan melalui kuesioner terstruktur dan rekam medis elektronik. Analisis data menggunakan uji statistik Chi-Square dan Prevalence Ratio (PR).Hasil penelitian mendapatkan 60,7% responden tidak memanfaatkan layanan. Variabel yang menunjukkan adanya hubungan yang signifikan adalah pendapatan (p=0,029; PR=1,475), keterpaparan informasi (p0,001; PR=3,017), serta persepsi estimasi waktu tiba (p=0,04; PR=1,521). Sedangkan variabel lain seperti jenis kelamin, tingkat pendidikan, persepsi biaya, persepsi jarak, dan status penyakit kronis tidak menunjukkan hubungan yang signifikan. Keterpaparan informasi merupakan faktor terkuat yang berhubungan dengan pemanfaatan layanan. RSUD Balaraja Kabupaten Tangerang perlu membuat strategi sosialisasi mengenai layanan, studi perbandingan mengenai tarif layanan pengantaran pada, serta kecepatan pengiriman atau estimasi waktu tiba obat untuk semua wilayah cakupan, dapat tiba di hari yang sama. Kata Kunci: Layanan Pengantaran Obat, Pemanfaatan Layanan Kesehatan, Keterpaparan Informasi, Pendapatan, Persepsi Estimasi Waktu Tiba.